2021
DOI: 10.3390/pathogens10111372
|View full text |Cite
|
Sign up to set email alerts
|

Highly Variable Clinical Pictures in Dogs Naturally Infected with Angiostrongylus vasorum

Abstract: Canine angiostrongylosis by Angiostrongylus vasorum is increasingly reported in both enzootic and previously free areas. The complex pathogenesis of the disease makes the clinical workup challenging. Infected dogs show highly variable clinical pictures, characterized by subclinical to life-threatening general, cardio-respiratory, neurological and/or gastrointestinal signs. The present study reports the high variability of clinical pictures from 36 dogs across central and southern Italy that were naturally infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 55 publications
1
13
0
Order By: Relevance
“…It is worthwhile to mention that the climate conditions for the year 2018 of gastropod collection were much warmer and drier than previous year meteorological records in these regions [ 62 ]. The influence of climatic conditions, such as extreme drought, on slug populations and metastrongyloid lungworm infections has been controversially discussed [ 1 , 32 , 34 , 45 , 49 , 65 ]. As such, temperature-driven influences on gastropod populations could be the following.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worthwhile to mention that the climate conditions for the year 2018 of gastropod collection were much warmer and drier than previous year meteorological records in these regions [ 62 ]. The influence of climatic conditions, such as extreme drought, on slug populations and metastrongyloid lungworm infections has been controversially discussed [ 1 , 32 , 34 , 45 , 49 , 65 ]. As such, temperature-driven influences on gastropod populations could be the following.…”
Section: Discussionmentioning
confidence: 99%
“…Assuming that the spread of A. vasorum can be triggered by different factors, such as intermediate host population dynamics and optimal environmental conditions, any means of early intervention to interrupt the parasite’s life cycle in regions where it has not yet disseminated into other intermediate host populations seems beneficial to combat further spreading. However, it can be challenging to identify early lungworm infections in dogs and cats, since clinical signs vary strongly and subclinical cases are common [ 3 , 11 , 64 , 65 , 67 ]. Hence, lungworm infections are easily overseen by both owners and veterinarians.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, diagnoses were made based on serum antigen detection, and a prevalence similar to those in this study was reported [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ], demonstrating that although prevalence is generally low, this disease is widely distributed throughout much of the continent, showing its emerging nature. Despite this, to date, there have only been two previous studies in Spain that have evaluated the presence of this disease in different regions, so an epidemiological map was needed to help determine the current status of canine angiostrongylosis in Spain [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This parasite can cause a wide range of clinical signs in the infected animal, including hemorrhagic (bleeding diathesis) and neurological signs. However, the most frequent clinical presentation is cardiorespiratory by nature, caused by the presence of adults and by the migration of larvae [ 8 , 9 ]. Fatal infection is often associated with severe respiratory compromise, pulmonary hypertension, right heart failure, and/or hemostatic dysfunction with fatal bleeding [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently reported clinical signs in dogs diagnosed with A. vasorum infection are related to the respiratory system. Depending on the population described, cardiorespiratory signs such as cough, dyspnea, and exercise intolerance occur in around 40-65% of cases [16][17][18]20]. However, the absence of respiratory signs does not exclude A. vasorum infection, regardless of the severity of clinical signs.…”
Section: Clinical Presentations Of Angiostrongylus Vasorum-infected Dogsmentioning
confidence: 99%